Studi Pengujian Tidak Merusak Ultrasonik pada Frekuensi 50 kHz untuk Modulus Elastisitas, Porositas, dan Kekuatan Tekan Beton - Rachmantyo, Riska; Nur Aziiz, Muhammad Sefano (LPPM ITK, 2023)
Important properties of structural materials, especially ceramics and concrete, are modulus of elasticity, porosity, and compressive strength. In the case of concrete, the modulus of elasticity of each material varies widely. The porosity created during the manufacturing process cannot be separated from the elastic modulus. Specimen testing methods typically involve compression testing, but only know the mechanical properties, not the porosity. The porosity of concrete materials can be measured using the non-destructive ultrasonic testing method. The modulus of elasticity to compressive strength can be measured froaamiim the resulting porosity value. Besides porosity, concrete properties are also affected by the water/cement ratio or w/c composition. Data from existing research results, which have certain limitations, were used in this research. The modulus of elasticity and compressive strength were calculated from the data of 39 ultrasonic tests of concrete samples with water/cement ratio variations ranging from 0.27 to 0.9 at a frequency of 50 kHz. Porosity ranged from 2.210% to 16.324% in the test results. According to the calculation, the average modulus of elasticity is 16.011 GPa and the average compressive strength is 13.36 MPa. As a result, porosity rises, reducing modulus of elasticity and compressive strength.